PENDERITAAN ORANG YANG TAK BERSALAH - Perspektif Fenomenologi Agama - Sermada Kelen Donatus (Studia Philosophica et Theologica, 2001)
The article is the modification of my paper seminar in German held in Bonn University 1992. The material was taken from the article of Prof. Hans-Joachim Klimkeit, “Der leidende Gerechte in der religionsgeschichte – Ein Beitrag zur problemorientierten “Religionsphänomenologie (the suffering of the just person in history of religion - a contribution to phenomenology of religion). The author modifies it and rewrites the idea in three parts: phenomenology of religion that exposes problem orientation, history of religion that articulates the reality of the suffering of the just, and the application of the topics in modern context of our life.